Stimuli-sensitive drug delivery systems for site-specific antibiotic release. Issue 6 (June 2022) - Nazir, Faiqa; Tabish, Tanveer A.; Tariq, Fatima; Iftikhar, Shanza; Wasim, Rijja; Shahnaz, Gul
Highlights: The stimuli leading to drug release can be either external or internal. Nanoparticles are promising agents for targeted stimuli-dependent antibiotic drugs delivery. Targeted antibiotic release at desired site minimizes the resistance and side effects associated with systematic release of drug(s). Abstract: Site-specific delivery of antibiotics has always been a high-priority area in pharmaceutical research. Conventionally used antibiotics suffer several limitations, such as low accumulation and penetration in diseased cells/tissues, limited bioavailability of drugs, drug resistance, and off-target toxicity. To overcome these limitations, several strategies have been exploited for delivering antibiotics to the site of infection, such as the use of stimuli-responsive antibiotic delivery systems, which can release antibiotics in a controlled and timely fashion. These stimuli can either be exogenous (light, magnetism, ultrasound, and electrical) or endogenous (pH, redox reactions, and enzymatic). In this review, we present a summary of recent developments in the field of stimuli-based targeted drug delivery systems for the site-specific release of antibiotics.